HCV Eradication with Direct-Acting Antivirals Does Not Impact HCC Progression on the Waiting List or HCC Recurrence after Liver Transplantation - Juliet A. Emamaullee; Mariusz Bral; Glenda Meeberg; Aldo J. Montano-Loza; Vincent G. Bain; Kelly Warren Burak; David Bigam; A. M. James Shapiro; Norman Kneteman (Canadian Journal of Gastroenterology and Hepatology)
Background. The introduction of direct-acting antivirals (DAA) for HCV has led to high rates of HCV eradication. Treatment of patients awaiting liver transplantation (LT) has been controversial. Recent data suggests that DAA treatment may accelerate recurrent HCC. The impact of DAA on delisting for HCC progression or recurrent HCC post-LT has not been well characterized. Methods. A retrospective review of both waitlist patients and LT recipients at a single institution was performed. Patient demographics, HCV treatment, HCC features and treatments, biopsy results, and graft and patient survival were evaluated. Patients on the LT waitlist or who were transplanted between January 2014 and December 2015 were included. Data was collected through December 2017 to have a minimum of two years of follow-up. Results. In the study period, 128 adult LT were performed. 44 patients were HCV+, and 68.2% (N=30) also had HCC. 38.6% (N=17) of HCV+ patients received DAA pre-LT, and 94.1% (N=16/17) achieved sustained virologic response (SVR) pre-LT. Among untreated HCV+ patients who underwent LT, 81.5% (N=22/27) received DAA post-LT, with 82.6% achieving SVR post-LT (N=18/22). 82.1% (N=23/28) of untreated post-LT patients underwent liver biopsy prior to therapy, and 52.2% had at least F1 METAVIR fibrosis. 87.5% (N=14/16) of active waitlist patients received DAA and achieved SVR. HCV eradication did not result in higher rates of delisting for HCC progression. Due to local HCC listing criteria of total tumor volume and AFP, 60% (N=18/30) of HCV+/HCC patients were beyond Milan criteria at the time of LT. Despite this, there was no difference in HCC recurrence rates post-LT, whether patients achieved SVR pre- or post-LT. Conclusions. These data suggest that HCV eradication pre-LT does not significantly impact waitlist time for HCV+ patients with HCC. HCV eradication does not impact rates of delisting for HCC progression or rates of HCC recurrence post-LT.